POLA PENGGUNAAN ANTIBIOTIK RESERVE DI UNIT INTENSIF DAN NON INTENSIF RAWAT INAP RSUP FATMAWATI - Subhan, Ahmad; Oktamauri, Ariesa; Haifa, Alifia; Wardani, Tita Kusuma (Jurnal Farmasi Klinik Best Practice, 2024)
The widespread prescription and utilization of antibiotics in hospitals globally, including Indonesia, pose a significant risk of inappropriate antibiotic usage, leading to antibiotic resistance. In response to this crisis, the World Health Organization (WHO) has devised the AWaRe (Access, Watch, Reserve) classification system. The use of reserve category antibiotics has been restricted. However, the available evidence is insufficient to draw definitive conclusions regarding the impact of these limitations and their correlation with patient clinical outcomes. This study aims to evaluate the usage patterns of reserve category antibiotics and their associated clinical outcomes in both intensive and non-intensive inpatient care at RSUP Fatmawati during the April - May 2024 period. Utilizing a prospective cohort design, the research subjects consisted of a total sampling of all inpatients who received reserve antibiotics. Statistical analysis was performed using SPSS 25. The largest proportion of reserve antibiotic use was observed in the ICU, accounting for 27.6%. The reserve antibiotics employed included Meropenem (83.71%), Aztreonam (2.33%), Cefepime (2.33%), Vankomisin (9.30%), and Ceftazidime (2.33%). These antibiotics were predominantly utilized for the diagnosis of sepsis & septic shock, constituting 72.10% of cases. The percentage of patients who received the correct antibiotic was 9.3%, with 75.0% experiencing improvement and 25.0% experiencing deterioration. Conversely, among patients receiving incorrect antibiotics, 48.7% experienced worsening. The inappropriate administration of antibiotics elevated the risk of patient deterioration (OR = 2.8; p = 0.359), with the most common inadequacies occurring in the duration and dosage of antibiotics.